Harnessing Project-Based Learning: The Implementation of the Pancasila Student Profile in Early Childhood Education - Syaikhu, Ahmad (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to explore the implementation of Project-Based Learning (PBL) in developing the Pancasila Student Profile in early childhood education (ECE) in West Jakarta. The research employs a quantitative approach, utilizing surveys with teachers. The survey results show that 91.7% of teachers have developed the Merdeka Curriculum in their teaching, and 91.7% of teachers also develop the Pancasila Student Profile within the Merdeka Curriculum. Additionally, 83.3% of teachers develop the Pancasila Student Profile in learning activities, and 91.7% of teachers develop Pancasila learning projects. Furthermore, 75% of teachers develop project-based learning in implementing the Pancasila Student Profile within the Merdeka Curriculum. The Pancasila Student Profile projects help 91.7% of teachers in managing learning and assist 83.3% of children in the learning process. However, only 8.3% of teachers find it difficult to implement the Pancasila Student Profile projects in learning. Despite challenges such as limited training and resource constraints, the benefits of PBL in increasing children's motivation and engagement are evident. This study underscores the need for increased support and training for teachers, as well as government support, to ensure the successful implementation of PBL in ECE.